EFFECTIVENESS OF THE CONCEPT OF MULTIPLICATION GROUPING AND NAPIER'S BONE TO IMPROVE MEMORY IN THE IMPLEMENTATION OF THE MERDEKA CURRICULUM - Nurdin Muhamad; Rudi Akmal (Universitas Majalengka, 2024)
This study evaluates the effectiveness of the multiplication grouping concept using Napier's bones to enhance memory, particularly in the context of implementing the independent curriculum post-COVID-19 pandemic. Employing a Posttest-only design, the research involved 609 students across 20 classes in four schools that had adopted the independent curriculum. The results of the T-test analysis rejected the null hypothesis, indicating that the multiplication grouping concept and Napier's bones significantly improved memory retention. These findings support the conclusion that the joint implementation of the independent curriculum using this method can be considered effective. Therefore, it is recommended to incorporate the multiplication grouping concept and Napier's bones as references in teaching, both inside and outside the classroom, to facilitate a more efficient understanding and operationalization of multiplication.